2004
DOI: 10.1596/1813-9450-3220
|View full text |Cite
|
Sign up to set email alerts
|

Public Management and Essential Public Health Functions

Abstract: This paper provides an overview of how different approaches to improving public sector management relate to so-called core or essential public health functions such as disease surveillance, health education, monitoring and evaluation, workforce development, enforcement of public health laws and regulations, public health research, and health policy development. The paper summarizes key themes in the public management literature and draws lessons for their application to these core functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 12 publications
0
29
0
2
Order By: Relevance
“…As this study showed, the problem was not simply about duplicate data sources; the major issue was that staff embroiled in these systems saw little personal use for such data, even as it was used as a disciplining tool against them and took up inordinate time. If anything, this case study suggests that the process of changing the broader institutional cultures and removal of old routines that can get in the way of creating a learning culture (Khaleghian and Das Gupta 2005;Mahler 1997;Potter and Brough, 2004) is a slow process. Realistically, institutionalizing and sustaining such change through a top-down approach may never work, but at a minimum, higher level administrators would have to support the shift toward "learning goals" and "outcome fidelity" to encourage and support cross-exchanges of the sorts of place-based indigenous approaches that were emerging here.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As this study showed, the problem was not simply about duplicate data sources; the major issue was that staff embroiled in these systems saw little personal use for such data, even as it was used as a disciplining tool against them and took up inordinate time. If anything, this case study suggests that the process of changing the broader institutional cultures and removal of old routines that can get in the way of creating a learning culture (Khaleghian and Das Gupta 2005;Mahler 1997;Potter and Brough, 2004) is a slow process. Realistically, institutionalizing and sustaining such change through a top-down approach may never work, but at a minimum, higher level administrators would have to support the shift toward "learning goals" and "outcome fidelity" to encourage and support cross-exchanges of the sorts of place-based indigenous approaches that were emerging here.…”
Section: Resultsmentioning
confidence: 90%
“…This is similar to Patton's (2010) "developmental evaluation" and Eyben's (2010) argument for a more "relationalist" approach to working through wicked problems, based on an iterative process, decentralized decision making, debate and disagreement, not just consensus, different paths to finding a solution, not just a unified approach, and "messy partnerships" (Guijt, 2008) that bring different actors together to discuss their partial understanding of a larger system. Finally, research shows that institutional reform requires changes to the broader structures that affect management and shape the organizational culture, including active efforts to encourage teamwork, reward innovation, increase staff exchanges, and support learning from failure (Khaleghian and Das Gupta, 2005;Potter and Brough, 2004;Tendler, 1997), and equally important, the removal of old routines that may conflict with new strategies to build a culture of learning (Mahler, 1997).…”
Section: Theories About Mande Effects On Policy Implementationmentioning
confidence: 99%
“…The population analysis has been performed by the natural bond orbital method at B3LYP/6-311G (d) level of theory using natural bondorbital (NBO) [37][38][39][40][41][42][43] .…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from the United States, the United Kingdom and Europe, as well as Australia and New Zealand, suggests that the new public management (NPM) is, but the contemporary response to the on-going process of change in public administration and governance since the late 18th Century (Boston, 2000;Barzelay, 2001;Khaleghian and Gupta, 2005). This period to date, has witnessed three separate, but continuous transformations in the context of governance and public administration.…”
Section: Historical Antecedents Of the New Public Managementmentioning
confidence: 99%